Reconstruction of the full-length transcriptome atlas using PacBio Iso-Seq provides insight into the alternative splicing in Gossypium australe - Feng, Shouli (BMC Plant Biol, 2019)
BACKGROUND: Gossypium australe F. Mueller (2n = 2x = 26, G(2) genome) possesses valuable characteristics. For example, the delayed gland morphogenesis trait causes cottonseed protein and oil to be edible while retaining resistance to biotic stress. However, the lack of gene sequences and their alternative splicing (AS) in G. australe remain unclear, hindering to explore species-specific biological morphogenesis. RESULTS: Here, we report the first sequencing of the full-length transcriptome of the Australian wild cotton species, G. australe, using Pacific Biosciences single-molecule long-read isoform sequencing (Iso-Seq) from the pooled cDNA of ten tissues to identify transcript loci and splice isoforms. We reconstructed the G. australe full-length transcriptome and identified 25,246 genes, 86 pre-miRNAs and 1468 lncRNAs. Most genes (12,832, 50.83%) exhibited two or more isoforms, suggesting a high degree of transcriptome complexity in G. australe. A total of 31,448 AS events in five major types were found among the 9944 gene loci. Among these five major types, intron retention was the most frequent, accounting for 68.85% of AS events. 29,718 polyadenylation sites were detected from 14,536 genes, 7900 of which have alternative polyadenylation sites (APA). In addition, based on our AS events annotations, RNA-Seq short reads from germinating seeds showed that differential expression of these events occurred during seed germination. Ten AS events that were randomly selected were further confirmed by RT-PCR amplification in leaf and germinating seeds. CONCLUSIONS: The reconstructed gene sequences and their AS in G. australe would provide information for exploring beneficial characteristics in G. australe. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1968-7) contains supplementary material, which is available to authorized users.